Counselor’s Code of Ethics in the Perspective of Islamic Education - Johan, Budi; Nate, Fitria; Dewanti, Nur Aulia Dwi; Fatihah, Tsalsa Amani; Syahman, Yudhia Az-Zahra; Rahman, Zaizul Bin Ab (Program Studi Bimbingan dan Konseling Islam, 2025)
In the modern era, the role of counselors as moral agents who transmit noble values is crucial, especially in Muslim-majority Indonesia, requiring counselors to have a deep understanding of Islam and moral integrity. This study aims to formulate and analyze the counselor’s code of ethics in detail from the perspective of Islamic Education. A qualitative approach using library research was employed, with primary data from the Qur’an and Sunnah, and secondary data from interpretations, hadith, fiqh, and scientific journals. The results show that the counselor’s code of ethics in Islam enriches professional standards with theological values such as human fitrah, amanah (trustworthiness), adl (justice), ihsan (goodness/excellence), maslahah (public interest), and tawakal (reliance on God) alongside ikhtiar (effort). Muslim counselors are also expected to emulate prophetic traits like shiddiq (truthfulness), amanah (trustworthiness), fathonah (intelligence), and tabligh (conveying truth/social concern), serving as spiritual role models. The application of these principles includes maintaining confidentiality as a trust, respecting individual dignity without discrimination, and being morally and professionally responsible. The integration of these Islamic values has been proven to enhance the quality of counseling services and strengthen professionalism, helping clients find meaning in life and spiritual strength. This research provides deep insights into the counselor’s code of ethics and guidance for education practitioners to improve their practices in accordance with more concrete ethical principles.